ASSESSMENT OF PUBLIC SPACE QUALITY OF DISTRICT CENTERS IN DELHI USING GOOD PUBLIC SPACE INDEX - Kaur, Simranpreet; Chhabra, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Public Spaces are a representative image of a city and play a vital role in maintaining social quotient of its people. Social interactions are a part of human nature for healthy and happy lifestyle. These interactions can happen with anybody and everybody varying from person to person. District centers are a typology of public spaces conceived in a master plan as part of mandatory commercial quotient in a neighborhood. In Delhi, these district centers are fundamental for public gatherings as they possess active and passive commercial spaces, retail, offices, food outlets and much more. This research paper aims to examine the qualitative aspects of these district centers with respect to good public space index (GPSI) given by researcher Vikas Mehta via primary surveys and public interaction. The study is a part of bigger research problem of evaluating publicness of Indian public spaces. It covers key attributes of a public space and people’s perception of it, followed by recommendations to enhance the value of urban public spaces.